2022
DOI: 10.3389/fpsyg.2022.989572
|View full text |Cite
|
Sign up to set email alerts
|

Collective intelligence in teams: Contextualizing collective intelligent behavior over time

Abstract: Collective intelligence (CI) in organizational teams has been predominantly understood and explained in terms of the quality of the outcomes that the team produces. This manuscript aims to extend the understanding of CI in teams, by disentangling the core of actual collective intelligent team behavior that unfolds over time during a collaboration period. We posit that outcomes do support the presence of CI, but that collective intelligence itself resides in the interaction processes within the team. Teams beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 126 publications
0
2
0
1
Order By: Relevance
“…In human‐only teams, for instance, positive predictor‐response and moderating relationships have been found between team performance and a variety of collective properties, including collective orientation—,that is, the tendency and willingness to work collectively in team scenarios—in complex problem solving scenarios, 20 and team cohesion as both a predictor of performance and a moderating factor between efficacy and performance 21,22 . Beyond outcome analysis, there is also evidence that other desirable team attributes are better understood with a collective perspective; Janssens et al., for instance, provide evidence that collective intelligence is best observed and measured not only through task outcomes but through the team's interactions, which, in turn, depend on the team's organization and information flow 23 …”
Section: Introduction and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In human‐only teams, for instance, positive predictor‐response and moderating relationships have been found between team performance and a variety of collective properties, including collective orientation—,that is, the tendency and willingness to work collectively in team scenarios—in complex problem solving scenarios, 20 and team cohesion as both a predictor of performance and a moderating factor between efficacy and performance 21,22 . Beyond outcome analysis, there is also evidence that other desirable team attributes are better understood with a collective perspective; Janssens et al., for instance, provide evidence that collective intelligence is best observed and measured not only through task outcomes but through the team's interactions, which, in turn, depend on the team's organization and information flow 23 …”
Section: Introduction and Approachmentioning
confidence: 99%
“…21,22 Beyond outcome analysis, there is also evidence that other desirable team attributes are better understood with a collective perspective; Janssens et al, for instance, provide evidence that collective intelligence is best observed and measured not only through task outcomes but through the team's interactions, which, in turn, depend on the team's organization and information flow. 23 Keeping the team as our central point of analysis, the framework we develop ultimately identifies the critical elements that characterize teaming and lays out categories for metrics as an extension of that. In many cases, we provide precise definitions of specific metrics and measures, either with our own, new definition or using a prior source, although some of our metrics are left broadly defined as classes of potential metrics focused on a narrower factor or set of factors.…”
mentioning
confidence: 99%
“…соціальним інтелектом, під яким розуміється «… -відносно стійка форма спільної розумової діяльності (здатності) людей, що виявляється в їх загальній творчості, виробленні і реалізації рішень, розумінні ними самих себе, інших людей і спільнот, навколишнього світу» [6]. Отже, саме соціальним, «інтегральним» [7] або ще «колективним» [8] інтелектом формується психологічноментальний фундамент взаємовідносин як між групами і спільнотами людей як в окремих державах, так і між множинами людей однієї державної спільноти з множинами інших державних спільнот.…”
unclassified